Sinergisme In Vitro Sulbactam-Cefoperazone dan Fosfomycin Terhadap Escherichia Coli dan Klebsiella Aeromobilis Di Indonesia - Agus Syahrurachman; Atna Permana (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: There is no susceptibility data of E. coli and K. aeromobilis in Indonesia, even data regarding minimal inhibitory concentration (MIC)-based susceptibility of E. coli and K. aeromobilis towards single antibiotic or combination of fosfomycin (FOS) and sulbactam-cepoferazone (SUL-CPZ) is very scarce, even though the data is required by clinicians. Methods: A descriptive observational study was carried out at the Microbiology Clinical Laboratory of the Faculty of Medicine, Universitas Indonesia. Thirty strains each of clinical isolates of E. coli and K. aeromobilis were subjected to MIC determination against FOS and SUL-CPZ. For susceptibility criteria, we adopted the Eucast guideline. The synergism of the combined antibiotics was determined by checkerboard titration. One strain of E. coli and K. aeromobilis showing a synergistic and independent effect against the combined antibiotics was subjected to a time-kill assay. The post-antibiotic effect (PAE) was determined on a strain of E. coli showing synergism against the combined antibiotics. Results: The MIC level of all strains decreased when the bacteria were exposed to the combined antibiotics. Synergism was observed in 53.3% of E. coli and 56.8% of K. aeromobilis. No antagonism was observed. Higher bacterial death during the first four hours occurred with the isolate, showing synergism compared to the isolate showing an independent effect. The PAE of E. coli was longer when exposed to combined antibiotics. Conclusion: In vitro synergism of FOS and SUL-CPZ was observed in the majority of isolates and could be used as the basis for further research on empirical treatment